Worthy: a collection of poetry - Harrison, Meghan Rose (2023)
Worthy is a collection of poetry aimed at uncovering and rediscovering a spirituality that rejects my Mormon and patriarchal upbringing, instead finding a newly defined faith rooted in femininity, wildness, and intuition. The collection walks readers through my deconstruction of not just the teachings of the Church of Jesus Christ of Latter-day Saints, but all Christianity. It explores the complex and rippling effects of my decision to leave the church I was raised in and married in, including the effects on my relationships with my husband, children, extended family, and friendships—as well as the ever-expanding relationship with my past, present, and future self. Though autobiographical and specific to Mormonism, these poems transcend my singular life and connect with women in our sisterhood, examining and celebrating how motherhood, marriage, religion, and the inevitability of aging change the way and things women write about and experience life. Themes such as the power of names/naming, grief, anger, wilderness and Earth, sexuality, and bodies are explored through lyrical and accessible language. There are a few poems that quote materials published by the LDS church in order to contextualize some of the vocabulary and situations that are unique to Mormonism, so readers of all (or no) faith background can understand and relate to the circumstances that surround each poem. My poetry collection will contribute to a small but growing community of “ex-Mormon” women writers, as well as women the world over who have become disenchanted with patriarchal-based, organized religion in general.